Transparency in Central Bank Financial Statement Disclosures - Sullivan, Kenneth (IMF Working Papers; Working Paper ;, 2000)
The IMF's development of the code of good practices on transparency in monetary and financial policies and introduction of safeguard assessments has increased the importance of the transparency of the disclosures found in central bank financial statements. This study looks at the disclosure requirements for central banks under International Accounting Standards and provides practical guidance for those responsible for preparing central bank financial statements.